ENHANCING ALFALFA PRODUCTION IN MARGINAL SANDY SOILS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Alfalfa is one of the forage crops widely cultivated due to its adaptability on differentsoil and environmental conditions. This forage crop is cultivated in more than 80 countries withover 210 million tons of alfalfa hay produced. The soils of the UAE are dominantly sandy andinfertile and hence show poor physical, chemical and fertility properties, suggesting frequentirrigation and replenishment nutrients based on crop requirement. Among other forages alfalfa isgrown in many farms. Sustainable agriculture production system plays an important role in creatingthe options that enable sustainability by developing systems that are environmentally preferable,more resource-efficient, and often more cost-effective (Gupta RJ et al, 2009). Desert sandy soilsare low in inherent soil fertility and due to high drainage capacity there are significant lossesof nutrients and water. High temperature, water scarcity and salinity are other constraints limitingagricultural production in desert environment (Suarez et al, 2010).Salinity and drought, two very closely associated abiotic stressors, negatively affect cropproductivity (Gamalero et al., 2020). Almost 20 % of the total irrigated land has been degraded dueto excess soil salinity (FAO, 2020). To meet the food, fodder, biomass energy, value-added productand employment requirements of the expanding population, it is critical to developing sustainableagricultural systems under constricted conditions in these marginal lands.
Keywords: Alfalfa, sustainable agriculture, fodder, legumineous forages, biomass production.